2008
DOI: 10.1111/j.1440-0960.2008.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapy‐related leukaemia cutis: A review

Abstract: Leukaemia cutis following chemotherapy for a malignancy is a multifactorial process that is dependent on the chemotherapeutic agent used, the dosing regimen, and the cumulative dose as well as potential contributing therapies such as radiation and possibly even hematopoietic support from granulocyte colony stimulating factor. In the right combination and in a patient with a conducive milieu of epigenetic factors, leukaemia can develop as a treatment complication. Leukaemia cutis is the specific infiltration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…35,37 Isolated cases have been described in the setting of Philadelphia chromosome-positive biphenotypic leukemias. 23,44,45 Therapy-related leukemias because of topoisomerase II inhibitors tend to present sooner after therapy than those because of alkylating agents and have monocytic differentiation, commonly because of the MLL rearrangement, fitting with our patient's presentation. 36 Otsubo et al 26 reported the development of an acute promyelocytic leukemia after ALC in association with NPM-RARA fusion transcript in a child.…”
Section: Discussionmentioning
confidence: 80%
“…35,37 Isolated cases have been described in the setting of Philadelphia chromosome-positive biphenotypic leukemias. 23,44,45 Therapy-related leukemias because of topoisomerase II inhibitors tend to present sooner after therapy than those because of alkylating agents and have monocytic differentiation, commonly because of the MLL rearrangement, fitting with our patient's presentation. 36 Otsubo et al 26 reported the development of an acute promyelocytic leukemia after ALC in association with NPM-RARA fusion transcript in a child.…”
Section: Discussionmentioning
confidence: 80%
“…In this case the data indicates that the topoisomerase II inhibitor, doxorubicin, is the primary, albeit not sole, culprit agent. The characteristics of her leukaemia best fit the topoisomerase II‐related leukaemia profile 1 . There was a short latency period of 16 months, no preleukaemic phase, and a monocytic (M‐5) subtype AML.…”
Section: Discussionmentioning
confidence: 85%
“…Leukaemia associated with alkylating agents contrasts with leukaemias due to topoisomerase II inhibitors with respect to onset, presence or absence of a preleukaemic phase, classification, genetic aberrations, and prognosis 1 . These differences have allowed practitioners to determine the potential causative agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations